A new genus and endangered species of euptychiine butterfly from isolated mountains in southeastern Brazil (Lepidoptera: Nymphalidae: Satyrinae) - Zacca, Thamara; Cordeiro, Danilo Pacheco; Gonella, Paulo Minatel (Zootaxa, 2023)
Agojie rupicola gen. et sp. nov., a new genus and species of Euptychiina from the campos rupestres and granitic inselbergs of eastern Minas Gerais, southeastern Brazil, is herein described using comparative morphology and ecological data. Diagnoses, photos, and illustrations are also provided, in addition to a discussion on the putative systematic placement of the new taxa and its conservation status. Considering the collecting points, the estimated value for the extent of occurrence (EOO) is 100.263 km2 and the area of occupancy (AOO) is 20 km2, which combined with the reduced number of localities in which the species is known to occur, and the observed continuing decline of the quality of the habitat, we recommend that A. rupicola gen. et sp. nov. should be formally assessed as Endangered based on criteria B1+2(a,biii) of the International Union for Conservation of Nature (IUCN). The results presented here add to the increasing faunistic and floristic novelties that justify the priority for the conservation of these still scientifically underexplored Brazilian mountains.